The Effect of Jigsaw Technique on Writing Ability of Grade Tenth Students at SMA Negeri 1 Siantar - Lidya Rospita Purba; Selviana Napitupulu; Bertaria Sohnata Hutauruk (Formosa Journal of Science and Technology, 2024)
This research aims to determine if the jigsaw technique is effective for improving grammar mastery in writing recount texts compared to conventional methods. Using a quasi-experimental design, two classes of tenth-grade students at SMA Negeri 1 Siantar were studied. The experimental class was taught using the Jigsaw technique, while the control class used conventional methods. Both classes received pretests and posttests to assess their understanding. The experimental class's average scores increased from 54 to 80.46, whereas the control class's scores rose from 53.21 to 71.21. The results, with a t-value of 2.44 compared to a t-table value of 2.00, indicate that the Jigsaw technique significantly improves students' ability to write recount texts, rejecting the null hypothesis.